An Insight to Brain Targeting Utilizing Polymeric Nanoparticles: Effective Treatment Modalities for Neurological Disorders and Brain Tumor - Annu,; Sartaj, Ali; Qamar, Zufika; Md, Shadab; Alhakamy, Nabil A.; Baboota, Sanjula; Ali, Javed (Frontiers in Bioengineering and Biotechnology, 2022)
The delivery of therapeutics molecules to the brain remains an unsolved problem to the researchers due to the existence of blood brain barrier (BBB) which halts the entry of unwanted substances to the brain. Central nervous system (CNS) disorders mainly Parkinson’s disease, Alzheimer’s disease, schizophrenia, brain tumors, and stroke are highly prevalent globally and is a growing concern for the researchers due to restricting delivery of pharmaceutical drugs to the brain. So, effective treatment modalities are essential to combat the growing epidemic of CNS diseases. Recently, the growing attention in the field of nanotechnology have gained the faith of researchers for delivery of therapeutics to the brain by targeting them to the specific target site. Polymeric nanoparticles (PNPs) emerge out to be an instrumental approach in drug targeting to the brain by overcoming the physiological, biomedical, and BBB. Preclinical discovery has shown the tremendous potential and versatility of PNPs in encapsulating several drugs and their targeting to deepest regions of brain thus improving therapeutic intervention of CNS disorders. Current review will summarize advances in the development of PNPs for targeting of therapeutics to the brain and the functional and molecular effects obtained in preclinical model of most common CNS diseases. The advancement of PNPs in clinical practice and their future prospect in brain targeting will also be discussed briefly.